British imperialism in Cyprus, 1878-1915 the inconsequential possession - Varnava, Andrekos 1979- (Studies in imperialism, 2015)
This book explores how the Union Jack came to fly over the island of Cyprus and why after thirty-five years the British wanted it lowered. Cyprus’ importance was always more imagined than real and was enmeshed within widely held cultural signifiers and myths